'Community Music' in Germany? An attempt to untangle German and English concepts in the context of music and pedagogy. Issue 1 (1st March 2016) - Josties, Elke
Which concepts come into play in the context of music and pedagogy? Why do German institutions tend to favour English terms such as 'education'? Why does a concept like 'Community Music' have no simple German translation – and why does it evoke irritating associations of 'music abuse' in 20th century German history? How can we characterize the tradition and profile of music education in German youth work today? What would we achieve by introducing 'Community Music' as a theoretical, musical-pedagogical concept to discourses on cultural education? And how can we define 'Community Music' in the German context? Why is the more artistically/aesthetically, pedagogically oriented Kulturelle Bildung of central interest in Germany? Does a new concept like Community Music threaten to crush the achievements of music-based children's and youth work? This essay is an attempt to untangle German and English concepts in the context of music and pedagogy. The author predicts that the term 'Community Music' will establish itself in Germany – similar to how 'education' has already established itself. This term will put a new label on old knowledge, strengthen or endanger established fields of practice, initiate new musical-pedagogical discourses and projects, but also evoke a host of vague associations.